Isoprostan Urin Sebagai Biomarka Keracunan Etanol dan Upaya Detoksikasinya dengan Ekstrak Etanol Kulit Buah Manggis (URINE ISOPROSTANE AS TOXIC BIOMARKER OF ETHANOL AND DETOXICATION EFFORTS BY USING ETHANOL EXTRACT OF SKIN MANGOSTEEN) - Suaniti, Ni Made; Manurung, Manuntun (Jurnal Veteriner; Vol 17 No 4 (2016), 2017)
Isoprostane as a marker of oxidative stress which is a toxic metabolite of fatty acids, can be formedafter experiencing lipid peroxidation duo to ethanol. The aim of this study was to analyze the isoprostaneas early detection biomarker in urine of Wistar rats after ethanol consumption in sub-acute, followed byadministration of ethanol extract of rind of mangosteen fruit (EERMF). ELISA was use in this study fordiagnostic method as it can analyze the content of biological fluids even in small amount. Detection ofisoprostane compounds in the urine Wistar rats after ingestion of ethanol 20%v/v in sub acute was (0.8837± 0.0625) ng/mL decrease levels (0.4500 ± 0.0625) ng/ mL after administration EERMF 20% w/v. Isoprostancan be used as biomarker ethanol toxic and decreased level after giving EERMF.
Keywords: isoprostane, ethanol, rind of mangosteen fruit,Garcia mangostana L.